Social representations of the democracy. Cognitions and attitudes in 34 nations - Grecu, Silviu-Petru (Technium Social Sciences Journal, 2021)
This article aims to emphasize the role played by social representations for understanding democracy. In this context, the article is relevant for both political psychology and political normative theory. At the empirical level, the study has several research objectives like: i. to analyse the importance of democratic order in different geographical areas; ii. to estimate several determinants of the satisfaction with democracy; iii. to estimate a model based on social representations of the democratic order. In correlation with the research objectives, empirical findings present three main variables which are related with the satisfaction with democracy (economy, political elite and gender equality with p <0.01). In this context, subjective perception of the economic welfare and political elite are classical variables for explaining the dynamic of democracy. Beyond traditional and liberal framework of understanding democratic order, gender equality is relevant for more than 70% of the statistical sample. In this context, political theory should be nuanced by the empirical findings and should develop a discreet normative framework for understanding the psychological dimension of the democracy.